2011
DOI: 10.14706/jecoss11123
|View full text |Cite
|
Sign up to set email alerts
|

Econometric Analysis of Import and Inflation Relationship in Turkey between 1995 and 2010

Abstract: In economics, the relation between import volume and inflation rate has been discussed several times for different countries. This study investigates the relationship between inflation and import volume by using monthly time series data for the Turkish economy over the period [1995][1996][1997][1998][1999][2000][2001][2002][2003][2004][2005][2006][2007][2008][2009][2010]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 17 publications
(16 reference statements)
0
2
0
1
Order By: Relevance
“…Some studies have found imported items to be a significant determinant of inflation (Richard & Michael, 1980). Earlier studies found that imports and inflation had a cointegration relationship (Ulke & Ergun, 2011). Other studies established a causal linkage between inflation and imports (Muktadir-Al-Mukit et al, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some studies have found imported items to be a significant determinant of inflation (Richard & Michael, 1980). Earlier studies found that imports and inflation had a cointegration relationship (Ulke & Ergun, 2011). Other studies established a causal linkage between inflation and imports (Muktadir-Al-Mukit et al, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, the effect of inflation on imports and consequently on total trade and balance of trade is insignificant. The main reason for such figures might be the higher importance of prices in the exporter countries in comparison with their prices in the importer countries (Islam 2013; Ahmed et al 2018; Ulke and Ergun 2011).…”
Section: Empirical Analysismentioning
confidence: 99%
“…Hal ini dikarenakan semakin tinggi tingkat inflasi yang menandakan naiknya harga barangbarang dan terus menerus, sehingga impor akan meningkat dengan harga barang impor yang lebih rendah dibandingkan dengan barang dalam negeri. Hasil ini juga sejalan dengan penelitian (Ulke, 2011) dalam Econometric Analysis of Import and Inflation Relationship in Turkey Between 1995 and 2010 yang menyatakan bahwa inflasi mempunyai hubungan yang searah terhadap volume impor.…”
Section: Inflasiunclassified